H α emission in local galaxies: star formation, time variability, and the diffuse ionized gas. Issue 2 (24th March 2022) - Tacchella, Sandro; Smith, Aaron; Kannan, Rahul; Marinacci, Federico; Hernquist, Lars; Vogelsberger, Mark; Torrey, Paul; Sales, Laura; Li, Hui
ABSTRACT: The nebular recombination line H α is widely used as a star formation rate (SFR) indicator in the local and high-redshift Universe. We present a detailed H α radiative transfer study of high-resolution isolated Milky-Way and Large Magellanic Cloud simulations that include radiative transfer, non-equilibrium thermochemistry, and dust evolution. We focus on the spatial morphology and temporal variability of the H α emission, and its connection to the underlying gas and star formation properties. The H α and H β radial and vertical surface brightness profiles are in excellent agreement with observations of nearby galaxies. We find that the fraction of H α emission from collisional excitation amounts to f col ∼ 5–10 per cent, only weakly dependent on radius and vertical height, and that scattering boosts the H α luminosity by 40 per cent . The dust correction via the Balmer decrement works well (intrinsic H α emission recoverable within 25 per cent), though the dust attenuation law depends on the amount of attenuation itself both on spatially resolved and integrated scales. Important for the understanding of the H α–SFR connection is the dust and helium absorption of ionizing radiation (Lyman continuum [LyC] photons), which are about f_abs≈ 28 per cent and f_He≈ 9 per cent, respectively. Together with an escape fraction of f_esc≈ 6 per cent, this reduces the available budget for hydrogen line emission by nearly half (f_H≈ 57 per cent ). We discuss the impact of the diffuse ionized gas, showing – among other things – that the extraplanar H α emission is powered by LyC photons escaping the disc. Future applications of this framework to cosmological (zoom-in) simulations will assist in the interpretation of spectroscopy of high-redshift galaxies with the upcoming James Webb Space Telescope .